2016
DOI: 10.5114/wo.2016.61845
|View full text |Cite
|
Sign up to set email alerts
|

Notch signalling pathway as an oncogenic factor involved in cancer development

Abstract: Notch signalling is an evolutionarily conserved signalling pathway, which plays a significant role in a wide array of cellular processes including proliferation, differentiation, and apoptosis. Nevertheless, it must be noted that Notch is a binary cell fate determinant, and its overexpression has been described as oncogenic in a broad range of human malignancies. This finding led to interest in therapeutically targeting this pathway especially by the use of GSIs, which block the cleavage of Notch at the cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…37 The regulatory function of Notch signaling in genes' expression often promote tumor formation. 40 Therefore, in this study, we explored the regulatory relationship between HNF1A-AS1 and Notch signaling in OSCC. We found that both HNF1A-AS1 and Notch signaling were upregulated in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…37 The regulatory function of Notch signaling in genes' expression often promote tumor formation. 40 Therefore, in this study, we explored the regulatory relationship between HNF1A-AS1 and Notch signaling in OSCC. We found that both HNF1A-AS1 and Notch signaling were upregulated in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…With miR-34a upregulation, its target genes Notch1, Notch2 and Bcl-2 were repressed following EESP treatment. Since these target genes were oncogenes and had apoptosis-targeting therapeutic potential in cancers (45)(46)(47), the results suggested that EESP might suppress growth of human colon carcinoma cells through promoting cell apoptosis by targeting Notch1, Notch2 and Bcl-2 via activating miR-34a ( Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to explore the structure and functional features of these ncRNAs, as well as their effects on malignancies. In therapy, contraposing the oncogenic potential of Notch signaling, Notch inhibitors including γ-secretase inhibitors (GSIs), are effective in inhibiting Notch signaling (4). GSIs have been demonstrated to prevent cell proliferation, migration and invasion in pancreatic cancer (100).…”
Section: Resultsmentioning
confidence: 99%
“…Based on its influence on various downstream functions, Notch signaling may serve oncogenic and anti-tumor functions in different types of human cancer, depending on the cellular context (22)(23)(24). In specific types of tumor or tumor stages, aberrant Notch signaling is involved in cancer recurrence, metastasis, epithelial to mesenchymal transition (EMT) and resistance to treatment (4,(25)(26)(27)(28).…”
Section: The Notch Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation